Risk Factors and Incidence for In-Stent Restenosis with Drug-Eluting Stent: A Systematic Review and Meta-Analysis - Birong Liu; Meng Li; Jia Liu; Lihua Xie; Jiaqi Li; Yong Liu; Chaofeng Niu; Di Xiao; Jingen Li; Lijing Zhang (Reviews in Cardiovascular Medicine)
Background: Despite significant reductions in in-stent restenosis (ISR) incidence with the adoption of drug-eluting stents (DES) over bare metal stents (BMS), ISR remains an unresolved issue in the DES era. The risk factors associated with DES-ISR have not been thoroughly analyzed. This meta-analysis aims to identify the key factors and quantify their impact on DES-ISR. Methods: We conducted comprehensive literature searches in PubMed, EMBASE, Cochrane, and Web of Science up to 28 February 2023, to identify studies reporting risk factors for DES-ISR. Meta-analysis was performed on risk factors reported in two or more studies to determine their overall effect sizes. Results: From 4357 articles screened, 17 studies were included in our analysis, evaluating twenty-four risk factors for DES-ISR through meta-analysis. The pooled incidence of DES-ISR was approximately 13%, and significant associations were found with seven risk factors. Ranked risk factors included diabetes mellitus (odds ratio [OR]: 1.46; 95% confidence interval [CI]: 1.14–1.87), stent length (OR: 1.026; 95% CI: 1.003–1.050), number of stents (OR: 1.62; 95% CI: 1.11–2.37), involvement of the left anterior descending artery (OR: 1.56; 95% CI: 1.25–1.94), lesion length (OR: 1.016; 95% CI: 1.008–1.024), medical history of myocardial infarction (OR: 1.79; 95% CI: 1.12–2.86) and previous percutaneous coronary intervention (OR: 1.97; 95% CI: 1.53–2.55). Conversely, a higher left ventricular ejection fraction was identified as a protective factor (OR: 0.985; 95% CI: 0.972–0.997). Conclusions: Despite advancements in stent technology, the incidence of ISR remains a significant clinical challenge. Our findings indicate that patient characteristics, lesion specifics, stent types, and procedural factors all contribute to DES-ISR development. Proactive strategies for early identification and management of these risk factors are essential to minimize the risk of ISR following DES interventions. The PROSPERO Registration: CRD42023427398, https://www.crd.york.ac.uk/PROSPERO/display_record.php?RecordID=427398.